Effect of salinity on locomotor performance and thermal extremes of metamorphic Andean Toads (Rhinella spinulosa) from Monte Desert, Argentina. (May 2018) - Sanabria, Eduardo; Quiroga, Lorena; Vergara, Cristina; Banchig, Mariana; Rodriguez, Cesar; Ontivero, Emanuel
Abstract: Rhinella spinulosa is distributed from Peru to Argentina (from 1200 to 5000 m elevation), inhabiting arid mountain valleys of the Andes, characterized by salty soils. The variations in soil salinity, caused by high evapotranspiration of water, can create an osmotic constraint and high thermal oscillations for metamorphsed Andean toad ( R. spinulosa ), affecting their thermoregulation and extreme thermal tolerances. We investigated the changes in thermal tolerance parameters (critical thermal maximum and crystallization temperature) of a population of metamorphosed R. spinulosa from the Monte Desert of San Juan, Argentina, under different substrate salinity conditions. Our results suggest that the locomotor performance of metamorphs of R. spinulosa is affected by increasing salinity concentrations in the environment where they develop. On the other hand, the thermal extremes of metamorphs of R. spinulosa also showed changes associated with different salinity conditions. According to other studies on different organisms, the increase of the osmolarity of the internal medium may increase the thermal tolerance of this species. More studies are needed to understand the thermo-osmolar adjustments of the metamorphs of toads to environmental variability. Graphical abstract: fx1 Highlights: Exposure to high salt concentrations decreases the locomotor performance of Andean toads. We observed changes in thermal extremes (maximum and minimum) in different salt concentrations. The Andean toad have a hormesis response for the locomotor performance at different temperatures and salt concentration.